Grafting modification of okra mucilage: Recent findings, applications, and future directions. (15th October 2020) - Raj, Vinit; Shim, Jae-Jin; Lee, Jintae
Highlights: This review discusses advancements in the grafting modification of okra polymers. Various methods for okra polysaccharide extraction are highlighted. Synthetic strategies for the modification of okra polysaccharide are presented. Applications of okra polysaccharides in different industries are explored. This review highlights the need for further research on okra polysaccharides. Abstract: Okra polysaccharides are biocompatible polymers with antimicrobial, anticancer, hypoglycemic, and antioxidant characteristics and hence are used in different fields such as drug delivery, food industry, and wastewater treatment. Consequently, okra-polymer modification by different methods, such as grafting, to satisfy industrial demands is attracting much scientific attention. Although a large body of literature is available on the extraction of okra polysaccharides and their applications, little is known about their grafting modification. While crosslinking and binary grafting can help in the realization of the desired properties, these methods have not been widely used on okra polysaccharides. In this review, we highlight the different methods used for the extraction of okra polysaccharides and systematically summarize major findings on their grafting modification and applications in different industries. This information will help in designing experimental protocols for the modification of okra polysaccharides to suit future needs.